MENINGKATKAN KEMAMPUAN MENULIS POSTER MELALUI PEMANFAATAN APLIKASI CANVA - Azzah Fatmawati; Moh. Mu’minin (Jurnal Bastra (Bahasa dan Sastra), 2026)
The low ability of students at MTs 45 Patihan in writing poster texts, caused by the use of conventional learning media, underlies this study. Canva was applied as an interactive medium through a quantitative pretest-posttest one group design involving 28 eighth-grade students. Data were obtained from questionnaires, tests, and observations, and analyzed using SPSS 25 with validity, reliability, normality, linearity, and t-test. Findings showed that the average pretest score of 63.82 with 35.71% mastery increased to 82.68 with 89.29% mastery in the posttest. The t-test confirmed a significant effect of Canva (sig. 0.000 < 0.05). Thus, Canva is proven effective in improving students’ poster-writing ability in terms of content, structure, and visualization, while supporting their cognitive, affective, and psychomotor development in Indonesian language learning.